Potensi Nanoselulosa untuk Agen Slow Release Bahan Alam: Review : Potential of Nanocellulose for Slow-Release Agents of Natural Materials: Review - Aqila Putri, Salsabila; Febrianti, Ratih; Sunardi, Sunardi (Jurnal Jejaring Matematika dan Sains, 2020)
Cellulose is the most abundant polymer on earth consisting of ?-l, 4 glycoside rings bound to ?-D-glucose. Cellulose can be obtained from various wood and non-wood sources. Nanocellulose is one of the cellulose derivatives that have the potential to be developed as a carrier agent for natural materials to increase their bioactivity and bioavailability. Nanocellulose, which is cellulose with a nano-size (1-100 nanometer), has been proved as one of the functional material sources that have superior properties due to its attractive and excellent characteristics such as high aspect ratio, better mechanical properties, biocompatibility renewable, and abundance. This paper discusses the sources, production methods, and applications of nano cellulose as a slow-release agent for various natural materials to an applications of biomedical, cosmetic, and biotechnology.